Development of Digital Controller for BLDC Motor Using dsPIC Controller - Siti Khadijah Binti Abdul Aziz, Siti Khadijah (Universiti Teknologi Petronas, 2010)
This paper present a simulation report of back EMF sensing scheme, direct back EMF detection, for application of sensorless BLDC motor drives with a DSP based controller. The project is aim to investigate the performance digital controller for BLDC motor using dsPIC 33FJ32MC204 and to measure the motor control parameters through PWM and back EMF analysis. This digital signal processing integrated circuit provides developing sensored or sensorless BLDC and Permanent Magnet Synchronous Motor (PMSM) control applications. In this project, the author focus on sensorless BLDC motor.